Spatio‐temporal variations of Anopheles coluzzii and An. gambiae and their Plasmodium infectivity rates in Lobito, Angola. Issue 1 (5th June 2015) - Carnevale, Pierre; Toto, Jean‐Claude; Besnard, Patrick; Santos, Maria Adelaide Dos; Fortes, Filomeno; Allan, Richard; Manguin, Sylvie
ABSTRACT From 2003 to 2007, entomological surveys were conducted in Lobito town (Benguela Province, Angola) to determine which Anopheles species were present and to identify the vectors responsible for malaria transmission in areas where workers of the Sonamet Company live. Two types of surveys were conducted: (1) time and space surveys in the low and upper parts of Lobito during the rainy and dry periods; (2) a two‐year longitudinal study in Sonamet workers' houses provided with long‐lasting insecticide‐treated nets (LLIN), "PermaNet, " along with the neighboring community. Both species, An. coluzzii (M molecular form) and An. gambiae (S molecular form), were collected. Anopheles coluzzii was predominant during the dry season in the low part of Lobito where larvae develop in natural ponds and temporary pools. However, during the rainy season, An. gambiae was found in higher proportions in the upper part of the town where larvae were collected in domestic water tanks built near houses. Anopheles melas and An. listeri were captured in higher numbers during the dry season and in the low part of Lobito where larvae develop in stagnant brackish water pools. The infectivity rates of An. gambiae s.l. varied from 0.90% to 3.41%.